Reactions of nitrosovinylphosphonates with electron-rich alkenes and heterocycles - Lemos, A. (2012)
In the presence of a base, chlorohydroxyiminophosphonates are converted in situ into the corresponding transient nitrosovinylphosphonates, which react as heterodienes with electron-rich alkenes and heterocycles producing oxazines and open-chain oximes in moderate yields and good selectivity. This approach may be regarded as a new strategy for the synthesis of precursors of α-amino phosphonic acids.